UDAN POTIR: REPETOIR YANG PUNAH DARI GORDANG SAMBILAN DALAM KOMUNIKASI PEMBANGUNAN ISLAM DI TANAH MANDAILING - Matondang, Abdul Rahman; Yasir, Muhammad; Sukiman; Rubino (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study aims to analyze the extinction of Udan Potir's repertoire in the Gordang Sambilan game while in development communication in Mandailing land. The extinction came from a repertoire full of ecological meaning in the form of rhythmic calling for rain and worshiping other than Allah. The method used in this study is exploratory research by analyzing the extinction of the udan potir repetoir in rites using gordang Sambilan along with the development of Islam in the Mandailing land. Specifically, this research seeks to trace information related to the repetoir on part-time gordang players in Mandaling Natal Regency, North Sumatra Province. This research analysis uses the Servaes development communication approach which seeks to unravel the extinction of Udan Potir's repertoire by looking at the important aspect of considering the local context in designing a development communication strategy. The results of this study indicate that Udan Potir's repetoir has uniqueness in the space of Mandailing local wisdom, but the repetoir is full of shirk values from rhythmic processes that tend to be in trance and worship other than God which makes this repeto increasingly left behind until it becomes extinct in the Gordang Sambilan tradition. Therefore it is necessary Therefore, development communication is needed to find a middle way in preserving Gordang Sambilan without violating the religious values shared by the majority of the community. this can be done by looking for alternative lyrics or movements that are more in line with religious values, or by maintaining the repertoire within the scope of non-religious culture.